2008
DOI: 10.1111/j.1365-2516.2008.01759.x
|View full text |Cite
|
Sign up to set email alerts
|

Thrombelastographic monitoring of recombinant factor VIIa in acquired haemophilia

Abstract: Monitoring of the global haemostatic capacity is desired to optimize the treatment with bypassing agents in inhibitor patients. Thrombelastographic methods have been used in ex vivo studies and were suggested useful to evaluate the individual response to bypassing agents. This study aimed at assessing changes in thrombelastographic profiles and their association to clinical outcome in patients treated with recombinant factor VIIa (rFVIIa). Ten patients with acquired haemophilia were treated with rFVIIa for acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
36
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 19 publications
3
36
0
Order By: Relevance
“…(or MCF) response to rFVIIa has been observed previously [10,17,22,24,25] and it may be due to a relatively lower contribution of platelets to these parameters. These data may suggest that the hemostatic effects of rFVIIa and NN1731 can be monitored by the PCF and CEM parameters, respectively.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…(or MCF) response to rFVIIa has been observed previously [10,17,22,24,25] and it may be due to a relatively lower contribution of platelets to these parameters. These data may suggest that the hemostatic effects of rFVIIa and NN1731 can be monitored by the PCF and CEM parameters, respectively.…”
Section: Discussionmentioning
confidence: 55%
“…This is most likely because we are merely testing a one-time ex-vivo concentration, whereas bleeding patients tend to get repeated rFVIIa doses of 90 mg/kg every 2 h until a desired response is obtained. This hypothesis is corroborated by Dehmel et al who showed that in order to completely correct the TEG profile, in vivo rFVIIa doses tended to be greater than 90 mg/kg and administered at least every 2-4 h. Thus patients benefit from the accumulated total dose, and not just the first 90 mg/kg dose[24]. Secondly, how do ex-vivo spiking experiments correspond to in-vivo dosing?…”
mentioning
confidence: 87%
“…Given that carbon monoxide rapidly diffuses through plasma, our data support the concept that carbon monoxide released from CORM-2 modifies fibrinogen to improve coagulation kinetics. It is not likely that thrombin generation per se was increased with CORM-2, as improved thrombin generation is typically associated with a more rapid onset of coagulation (equivalent to TMRTG) when thrombelastography is used to assess coagulation kinetics [11,[13][14][15][16][17][18]. In summary, with only one exception observed in a FIX-deficient individual, CORM-2 improved the velocity of formation and strength in the deficient plasmas tested.…”
Section: Discussionmentioning
confidence: 93%
“…The modern treatment regimens in hemophilia with inhibitor help to decrease bleeding episodes, morbidity, and improve quality of life. [55][56][57][58][59][60][61][62][63][64] New therapeutic strategies are relatively expensive, and they are not affordable for underdeveloped and poor countries. 40,[64][65][66][67] Biosimilar products are comparable hemostatic agents to the branded product and provide better care and wider affordability.…”
Section: Discussionmentioning
confidence: 99%
“…to270 mg/kg, 2 hours apart, and have been used. We chose 90 to 120 mg/kg dosage, which is similar to other studies 21,[58][59][60][61][62][63][64]. Efficacy and reduction in bleeding were similar in both treatment groups.…”
mentioning
confidence: 98%